Synthesis and cycloaddition chemistry 1,3-Bis(phenylsulfonyl)propadiene - Desmond-Smith, Nicholas Stuart (Department of Chemistry, 2016)
An efficient synthesis of the highly activated I J-bis(phenylsulfonyl)propadiene is described. Starting from benzenesulfonyl chloride and propargyl bromide the key step of the synthesis is the addition of benzene sulfonyl iodide to phenylsulfonylpropyne. This is demonstrated to occur under thermal conditions in the presence of a radical initiator to obtain (E)-2-iodo-1 ,3-bis(phenylsulfonyl)prop-I-ene. Triethylamine induced dehydroiodination of the above addition product afforded high quality 1,3bis( phenylsulfonyl)propadiene after an aqueous reverse quench procedure without further purification. I ,3-Bis(phenylsulfonyl)propadiene was sho'TI to be stable under refluxing conditions towards diethyl ether, chloroform, ethyl acetate and benzene. Reaction with methanol occurred to yield (E)-2-methoxy-1 ,3-bis(phenylsulfonyl)prop-I-ene and with tetrahydrofuran to yield 2-(2-tetrahydrofuranyl)-(E)-1 ,3-bis(phenylsulfonyl)propene, in a novel insertion reaction. The homocyclisation of 1,3-bis(phenylsulfonyl)propadiene under thermal conditions was demonstrated to yield the highly substituted 2,7bis( phenylsulfonylmethylene)-3,4,5,6-tetraphenylsulfonyI-spiro[3.3.0]heptane. Reaction with cyclopentadiene, furan, butadiene and Danishefsky's diene has been conducted in a regio- and peri-selectivity study to yield the [4+2] cycloadducts. Treatment of the furan cycloadducts with potassium t-butoxide opened up the oxygen bridge of three of the furan cycloadducts and resulted in aromatisation to the 3-phenylsulfonyl-2phenylsulfonylmethylphenol. The remaining cycloadduct was converted to the phenol derivative by treatment with sodium hydride. Potassium methoxide treatment of the furan cycloadducts resulted in the isolation of a methoxide addition product together with the aromatised adduct. Procedures for the synthesis ofphenylsulfinylpropadiene and phenylsulfonylpropadiene are described.